2021
DOI: 10.1111/jvp.12949
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tolfenamic acid in goats after different administration routes

Abstract: The aim of this study was to determine the pharmacokinetics and bioavailability of tolfenamic acid in goats after intravenous (IV), intramuscular (IM), subcutaneous (SC), and oral (PO) administrations at 2 mg/kg dose. In this study, eight clinically healthy goats were used. The study comprised four periods, according to a crossover design with at least a 15‐day washout period between treatments. Plasma concentrations of tolfenamic acid were determined by HPLC‐UV, and the pharmacokinetic parameters were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
(93 reference statements)
3
11
1
Order By: Relevance
“…The elimination t 1/2ʎz of carprofen was 43.36 h, which was similar to the previously reported in calves (43.4 h, Delatour et al, 1996), and longer than that reported for sheep, dog, horse, cat, and cow (8.00–33.7 h, Lohuis et al, 1991; McKellar et al, 1990, 1991; Parton et al, 2000; Welsh et al, 1992). Carprofen has longer elimination t 1/2ʎz than other NSAIDs including tolfenamic acid, meloxicam, ketoprofen, and flunixin meglumine used in veterinary medicine (Corum et al, 2018; CVMP, 1995; Tekeli et al, 2020; Turk et al, 2021b; Welsh et al, 1993). The reason for the difference in the elimination t 1/2ʎz of carprofen in sheep may be due to the difference in breed (Akkaraman vs. Suffolk), weight (42.63 ± 3.38 vs. from 53 to 66 kg), and the sensitivity of analytical method (0.02 μg/ml vs. 0.1 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…The elimination t 1/2ʎz of carprofen was 43.36 h, which was similar to the previously reported in calves (43.4 h, Delatour et al, 1996), and longer than that reported for sheep, dog, horse, cat, and cow (8.00–33.7 h, Lohuis et al, 1991; McKellar et al, 1990, 1991; Parton et al, 2000; Welsh et al, 1992). Carprofen has longer elimination t 1/2ʎz than other NSAIDs including tolfenamic acid, meloxicam, ketoprofen, and flunixin meglumine used in veterinary medicine (Corum et al, 2018; CVMP, 1995; Tekeli et al, 2020; Turk et al, 2021b; Welsh et al, 1993). The reason for the difference in the elimination t 1/2ʎz of carprofen in sheep may be due to the difference in breed (Akkaraman vs. Suffolk), weight (42.63 ± 3.38 vs. from 53 to 66 kg), and the sensitivity of analytical method (0.02 μg/ml vs. 0.1 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in administering injectable drugs in some cases, alongside cost and time, are other reasons on the list too (Huxley & Whay, 2007 ; Lizarraga & Chambers, 2012 ). It should be noted that a few NSAIDs for sheep and goats are approved in some nations, such as Canada, New Zealand, Australia, India, Mexico, Peru, and Costa Rica (Anonymous, 2016 ; 2020 ; Turk et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of action of TA is the prevention of COX enzyme formation by prostaglandins through the inhibition of prostaglandin production throughout the body, which reduces inflammation, pain, and fever [10,11]. TA is rapidly absorbed and eliminated by the body with a short half-life (1.94-5.71 h) [12,13]. Currently, there are only two common dosage forms of TA available on the market, i.e., tablets and injections.…”
Section: Introductionmentioning
confidence: 99%